Swiftian Inspirations the Legacy of Jonathan Swift from the Enlightenment to the Age of Post-Truth. - McCreedy, Jonathan; Budakov, Vesselin M.; Glavanakova, Alexandra K. (Cambridge Scholars Publisher, 2020)
This book addresses key problems regarding Swiftian thought and satire, analyzing the inspirational cultural legacy which generations of writers, thinkers, and satirists have recurrently relied upon since the Enlightenment. Section One deals with the eighteenth century and the topics of truth, falsehood and madness. Section Two focuses on two film adaptations of Gulliver's Travels as well as on allusions to Swiftian satire during the US Enlightenment and in post-racial America. Section Three looks at the politics of language, politeness, and satire within translation, and Section Four dwells u.